Microsatellite-based analysis deciphers the uniqueness of three lesser-known Indian cattle populations - SHARMA, REKHA; AHLAWAT, SONIKA; PUNDIR, R K; DAS, SABYASACHI; ARORA, REENA; TANTIA, M S (The Indian Journal of Animal Sciences, 2023)
Indian cattle genetic resources constitute an important global gene pool. A majority of these (59.3%) are still not characterized. Identifying unique populations can ensure their inclusion in national policies of improvement and conservation. The present research describes the uniqueness of three lesser-known cattle populations (Jhari, Kamma, and Vandharvi) of Deccan Plateau region of India. These are known for draught power but are on the decline due to changing socio-agricultural scenario. Comprehensive genetic diversity and differentiation analyses using 25 FAOrecommended microsatellite markers identified high variability in all three populations with mean allelic diversity (Na) ranging between 9.32-9.80. Similarly, high genetic variability was recorded in all three populations (Ho=0.67 to 0.71). Random mating in the populations was indicated by the small positive F value. A low but significant genetic differentiation, pairwise Nei’s genetic distance, phylogenetic relationship, and genetic assignment substantiated their separate genetic identity. The phylogenetic analysis reflected the closeness of Vandharvi and Kamma populations. Substantial gene flow was evidenced by the effective number of migrants per generation (Nm=16.31±2.69 >1). Bayesian-based clustering indicated the germplasm exchange between Vandharvi and Kamma, whereas, Jhari comes out to be a separate gene pool. None of these have suffered demographic bottlenecks in the recent past. Findings arevaluable for the scientific management, recognition, and conservation of the three populations that contribute to the livelihood, and economic sustainability of agro-pastoral communities.